2019
DOI: 10.1186/s12879-019-4405-5
|View full text |Cite
|
Sign up to set email alerts
|

Detecting influenza and emerging avian influenza virus by influenza and pneumonia surveillance systems in a large city in China, 2005 to 2016

Abstract: Background Detecting avian influenza virus has become an important public health strategy for controlling the emerging infectious disease. Methods The HIS (hospital information system) modified influenza surveillance system (ISS) and a newly built pneumonia surveillance system (PSS) were used to monitor the influenza viruses in Changsha City, China. The ISS was used to monitor outpatients in two sentinel hospitals and to detect mild … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…This surge could reflect enhanced administrative requirements from health authorities or enhanced clinician awareness of respiratory viruses. 28 However, under-reporting by physicians still apparently happens quite frequently, either because the criteria for PUE notification are not well defined or because physicians are not aware of the requirement to report. 29 In summary, China has benefitted from international collaborations on building disease surveillance systems and the global health community has benefited from the access to infectious disease data and technical expertise in China.…”
Section: China's Infectious Disease Reporting Systemsmentioning
confidence: 99%
“…This surge could reflect enhanced administrative requirements from health authorities or enhanced clinician awareness of respiratory viruses. 28 However, under-reporting by physicians still apparently happens quite frequently, either because the criteria for PUE notification are not well defined or because physicians are not aware of the requirement to report. 29 In summary, China has benefitted from international collaborations on building disease surveillance systems and the global health community has benefited from the access to infectious disease data and technical expertise in China.…”
Section: China's Infectious Disease Reporting Systemsmentioning
confidence: 99%
“…Relevant studies have shown that the rate of avian influenza virus detection correlated with outbreaks to some extent, i.e . the higher the positive rate, the greater the possibility of an outbreak ( 10 ). Some studies have used positive samples of H7N9 to analyse the transmission regularity of the virus ( 1 , 11 ) and to judge the effect of closing live poultry markets ( 29 ) and comprehensive H7N9 immunisation of at-risk animals ( 30 ).…”
Section: Introductionmentioning
confidence: 99%